Electroencephalography (EEG) Features in Patients with Primary Headache at Neurology Polyclinic of Dr. M. Djamil Padang Hospital - Restu Susanti (Biomedical Journal of Indonesia, 2020)
Headache is one of the most common neurological complaints. The InternationalHeadache Society (IHS) classification divides headaches into a primary and secondary headache. The cause or type of headache can be determined from the history of the disease and physical examination. Neurophysiological tests are used in establishing a differential diagnosis of headache. There are several neurophysiological methods used in the diagnosis of headaches, one of them is electroencephalography. This study aims to look at the most frequent EEG picture in cases of a primary headache without focal neurological deficits in the Neurology Polyclinic of Dr. M. Djamil Padang Hospital from January 2019 to December 2019. This research used a descriptive method. The study population was all patients who underwent an EEG examination in the Integrated Diagnostic Installation (IDT) of Dr. M. Djamil Padang Hospital from January 2019 to December 2019. Subjects were patients who had a chief complaint of headache who had been subjected to an EEG examination. Statistical analyzes were performed computerized using IBM SPSS Statistics version 23.0 for Windows. From this study, the most common chronic headache is migraine, and the most common EEG feature is normal. EEG can be used as a modality for investigating chronic headaches without focal neurological deficits.